2011
DOI: 10.4274/tpa.45.137
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklarda sünnetin idrar yolu enfeksiyonu sıklığı üzerine etkisi

Abstract: Ç Ço oc cu uk kl la ar rd da a s sü ün nn ne et ti in n i id dr ra ar r y yo ol lu u e en nf fe ek ks si iy yo on nu u s s› ›k kl l› ›¤ ¤› › ü üz ze er ri in ne e e et tk ki is si i E Ef ff fe ec ct t o of f c ci ir rc cu um mc ci is si io on n o on n u ur ri in na ar ry y t tr ra ac ct t i in nf fe ec ct ti io on n i in n b bo oy ys s N Ni ih ha al l Ö Öz zd de em mi ir r, , H Ha ar ri ik ka a A Al lp pa ay y, , N Ne efl fle e B B› ›y y› ›k kl l› ›, , ‹ ‹b br ra ah hi im m G Gö ök kç çe e, , A Ah hm me et t T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have shown that circumcision decreases the frequency of urinary tract infection (UTI), sexually transmitted diseases, penile cancer and phimosis (2)(3)(4)(5)(6)(7)(8)(9). Boys have been circumcised for tousands years because of cultural and religious beliefs in some populations including mainly our country (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that circumcision decreases the frequency of urinary tract infection (UTI), sexually transmitted diseases, penile cancer and phimosis (2)(3)(4)(5)(6)(7)(8)(9). Boys have been circumcised for tousands years because of cultural and religious beliefs in some populations including mainly our country (10).…”
Section: Introductionmentioning
confidence: 99%